Revisions to the International Neuroblastoma Response Criteria: A Consensus Statement From the National Cancer Institute Clinical Trials Planning Meeting - Park, Julie R.; Bagatell, Rochelle; Cohn, Susan L.; Pearson, Andrew D.; Villablanca, Judith G.; Berthold, Frank; Burchill, Susan; Boubaker, Ariane; McHugh, Kieran; Nuchtern, Jed G.; London, Wendy B.; Seibel, Nita L.; et al. (Journal of clinical oncology, 2017)
Purpose More than two decades ago, an international working group established the International Neuroblastoma Response Criteria (INRC) to assess treatment response in children with neuroblastoma. However, this system requires modification to incorporate modern imaging techniques and new methods for quantifying bone marrow disease that were not previously widely available. The National Cancer Institute sponsored a clinical trials planning meeting in 2012 to update and refine response criteria for patients with neuroblastoma. Methods Multidisciplinary investigators from 13 countries reviewed data from published trials performed through cooperative groups, consortia, and single institutions. Data from both prospective and retrospective trials were used to refine the INRC. Monthly international conference calls were held from 2011 to 2015, and consensus was reached through review by working group leadership and the National Cancer Institute Clinical Trials Planning Meeting leadership council. Results Overall response in the revised INRC will integrate tumor response in the primary tumor, soft tissue and bone metastases, and bone marrow. Primary and metastatic soft tissue sites will be assessed using Response Evaluation Criteria in Solid Tumors (RECIST) and iodine-123 ( I) -metaiodobenzylguanidine (MIBG) scans or [ F]fluorodeoxyglucose-positron emission tomography scans if the tumor is MIBG nonavid. I-MIBG scans, or [ F]fluorodeoxyglucose-positron emission tomography scans for MIBG-nonavid disease, replace technetium-99m diphosphonate bone scintigraphy for osteomedullary metastasis assessment. Bone marrow will be assessed by histology or immunohistochemistry and cytology or immunocytology. Bone marrow with ≤ 5% tumor involvement will be classified as minimal disease. Urinary catecholamine levels will not be included in response assessment. Overall response will be defined as complete response, partial response, minor response, stable disease, or progressive disease. Conclusion These revised criteria will provide a uniform assessment of disease response, improve the interpretability of clinical trial results, and facilitate collaborative trial designs.